MANAJEMEN KONFLIK KELUARGA POLIGAMI DAN MONOGAMI - Tri Utami, Rini; Mawarpury, Marty (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2019)
Family conflict is a natural and common thing whether in polygamous or monogamous families. How to manage conflict can determine the impact of the conflict. The purpose of this study was tofind out the differences in conflict management between polygamous and monogamous families.This study used a quantitative approach with a non-probability sampling method using purposivesampling technique with 60 respondents (30 respondents from polygamous families and 30respondents from monogamous families). data was collected using conflict management scale, thatdeveloped by the researcher based on the theory of family conflict resolution. The result of ManWhitney Test showed that a significant value 0.358, which mean that there were no differencesbetween polygamous and monogamous families in managing conflict.